2020
DOI: 10.46897/livestockstudies.846415
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Some Environmental Factors on Lactation Length, Milk Yield and Calving Intervals of Anatolian Buffaloes in Bartın Province of Turkey

Abstract: This study aims to determine the environmental factors effected to lactation length (LL), lactation milk yield (LMY), calving intervals (CI) of Anatolian buffaloes in Bartın. In this study, 1511 milk yield data belonging to 762 Anatolian buffaloes and 957 CI data belonging to 543 Anatolian buffaloes which has been reared in different environmental conditions between 2015-2019 under the scope of the Anatolian Buffalo Breeding Project being conducted in Bartın province. The least squares method was used for dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 12 publications
3
3
0
Order By: Relevance
“…The differences in milk yield throughout the years stemmed from the level of farm management and environmental factors. In agreement with our study, the effects of calving year and age were significant in several studies (2,20,29). The highest TLMY value was observed in buffaloes calving at 9-10 years old, while the 3-to 4-year-old group produced the lowest TLMY.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The differences in milk yield throughout the years stemmed from the level of farm management and environmental factors. In agreement with our study, the effects of calving year and age were significant in several studies (2,20,29). The highest TLMY value was observed in buffaloes calving at 9-10 years old, while the 3-to 4-year-old group produced the lowest TLMY.…”
Section: Discussionsupporting
confidence: 94%
“…There are some studies reporting that the study region has a significant effect on TLSV. (2,28) In the present study, the effect of calving year on LL found significant (P<0.05) (Table 2). The results found in this study were similar to the Charlini and Sinniah (9), Koçak et al (20) and Alkoyak and Öz (2).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Soysal et al [ 78 ] described that LL was lower in the first parity, was constant from the second to the fourth parity, and then decreased, and the hot season negatively affected LL, reducing it by 29 days compared to the cold season in Anatolian buffalo (244.82 vs. 215.80 days for the winter and summer seasons, respectively). On Anatolian buffalo, Alkoyak and Öz [ 79 ] reported a negative effect for the hot season (in winter, 265.35 ± 4.09, and in summer, 251.68 ± 3.29), but instead, there was no difference between parity.…”
Section: The Effect Of Heat Stress On Buffalomentioning
confidence: 99%
“…The optimal CI for dairy buffalo should be 12–13 months [ 81 ]. Alkoyak and Öz [ 79 ] found that in Anatolian buffalo, the CI decreased in the summer and spring seasons by about 28 days compared to the winter season (390.28 ± 8.57, 390.62 ± 7.50, and 418.04 ± 9.34 days for the spring, summer, and winter seasons, respectively). Jakhar et al [ 76 ] observed a seasonal effect on the CI; it was lower in the summer and rainy season than in the winter for Murrah buffalo (463.73 ± 5.63, 471.43 ± 9.66, and 504.61 ± 6.24 days for the rainy, summer, and winter seasons, respectively).…”
Section: The Effect Of Heat Stress On Buffalomentioning
confidence: 99%